Analysis of PTKP Policy and Tax Rates on PPH 21 with Regulatory Literacy as Moderation - Rahayu, Iis Puji; Isnaniati, Siti; Selviasari, Rike (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Taxpayer compliance is a crucial factor in optimizing state revenue and sustaining fiscal policy. This study aims to analyze the influence of Non-Taxable Income (PTKP), tax rates, and regulatory literacy on individual taxpayer compliance, and to examine the role of regulatory literacy as a moderating variable. The study used a quantitative approach with regression analysis on individual taxpayer respondent data in selected regions. The results indicate that PTKP, tax rates, and regulatory literacy have a positive and significant effect on taxpayer compliance. Furthermore, regulatory literacy has been shown to strengthen the relationship between PTKP policy and taxpayer compliance, but does not moderate the effect of tax rates on compliance. These findings indicate that proportional fiscal policy, reasonable rates, and a sound understanding of regulations play a crucial role in fostering tax compliance. From an Islamic economic perspective, a fair, transparent, and maslahah-oriented fiscal policy aligns with the principles of al-'adl and amanah (trustworthiness), ensuring that tax compliance is not merely administrative but also a moral responsibility. This study recommends improving regulatory literacy as a strategic effort to strengthen taxpayer compliance sustainably.